Objectives of the Demonetisations in the World. Special Reference to Indian Demonetisation of 2016 - S. Khakase; D. Hawaldar (Финансы: теория и практика)
“Demonetisation” means the removal or rejection of one or more legitimate payment methods in the economy. This term is as old as the use of currency, which can be traced back to 7th and 6th centuries BCE. The Indian government conducted an unannounced demonetization in 2016. Similar cases were observed in India in 1946 and 1978. Overall, the world has witnessed dozens of demonetisations in different countries, which were carried out for different reasons. Many were successful, but many were not. We need to understand why demonetisation has been implemented over the world. This study used a literature review method to determine the causes of demonetisation in nations such as Australia, Canada, New Zealand, Libya, Ghana, Myanmar, Zaire, Russia, North Korea, Pakistan, Sweden, Zimbabwe, and Belarus. It also describes the goals of Indian demonetisation in 2016 and determines whether they have been met. As a result, the authors found that pre-announced demonetisation were usually effective, whereas most undeclared demonetisation failed and had an impact on the economy and population. The results of this paper can help governments, policymakers and scientists to understand the purpose of demonetisation and the need for caution. The authors concluded that demonetisation could have both positive and negative effects, depending largely on the intentions of the country’s leadership and on the preparedness for demonetisation.